Acute heart failure due to large intimal flap associated with chronic aortic dissection. Issue 12 (28th September 2020) - Tobinaga, Satoru; Satoh, Akira; Shintani, Yusuke; Tanaka, Hiroyuki
Abstract: Acute heart failure from aortic stenosis secondary to chronic aortic dissection is very rare. We describe a case of acute heart failure secondary to aortic arch stenosis resulting from subacute type A aortic dissection. Resection of large thickened immobile intimal flap with total aortic arch replacement was successful, and cardiac function improved.